Psychomotor delay, dysmorphsim and epilepsy with underlying genetic etiology: A case report of first child with a genetically confirmed diagnosis of Angelman Syndrome on a hospital-based setting in Iraq - Saadi, Nebal W. (Journal of the Faculty of Medicine Baghdad, 2016)
In this case report we discuss essential issue to be considered with regard to the clinical genetic testing in the epilepsies. The identification of genes that influence risk for the epilepsies has extremely important implications for both research and clinical practice. In a research context, information obtained may lead to the development of new treatments targeted to specific mechanisms, or even to ways of preventing epileptogenesis. In clinical practice, the use of genetic information can either clarify the diagnosis in people already known or suspected to have epilepsy (diagnostic testing), or to predict onset of epilepsy in people at risk of developing epilepsy because of a family history (predictive testing). This 8-year old girl presented because of rapid regression in the cognitive function and had disturbed consciousness which started few weeks before admission. History of delayed milestones, epilepsy, subtle facial dysmorphology, ataxic gait and happy demeanor collectively raised suspicion of genetic/metabolic disorder. Genetic study discovered a deletion involving the maternally derived chromosome 15q11 region and this deletion is associated with Angelman Syndrome.